FORMULATION AND ACTIVITY TESTS OF NANOEMULSION OF TURMERIC RHIZOME (CURCUMA LONGA L) EXTRACT FOR METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) BACTERIA - Syarifah, Arini; Azizah, Wafiqotul; Prasuma, Galar Sigit (Jurnal Farmasi Sains dan Praktis, 2024)
Turmeric rhizome (Curcuma longa L) contains the main active compound curcumin, which has antibacterial activity which inhibits Methicillin-Resistant Staphylococcus aureus (MRSA). Developing a nanoemulsion formula for turmeric rhizome extract can overcome bacterial resistance by protecting the active substance from degradation and blocking the efflux pump in bacteria. This research aims to create a nanoemulsion formulation and determine the activity of turmeric rhizome extract nanoemulsion against MRSA bacteria in vitro. Method: Turmeric rhizomes were extracted using the maceration method using 70% ethanol solvent. The technique of nanoemulsion preparation was by using the spontaneous emulsification method with varying extract concentrations of 1.25% (F1), 2.50% (F2), and 3.75% (F3). Evaluation of the physical characteristics of nanoemulsions includes particle size, polydispersity index, zeta potential, viscosity, and pH. In vitro activity test of turmeric rhizome extract nanoemulsion using the diffusion method against MRSA bacteria. The turmeric rhizome extraction process produces a yield value of 14.3%. The best formula for turmeric rhizome extract nanoemulsion is F1 with a viscosity value of 134.6 ± 21.3 Cps, pH value of 6.34, particle size value of 33.4 ± 12.8 nm, polydispersity index of 0.407 ± 0.01, zeta potential -14.2±2.9 mV. Turmeric extract nanoemulsion can inhibit the growth of Methicillin-Resistant Staphylococcus aureus bacteria with an inhibition zone of 11.00 mm at F3. Conclusion: Curcumin can be formulated in a nanoemulsion system without providing significant changes in organoleptic tests, viscosity, pH, nanoemulsion type tests, particle size, polydispersity index, and zeta potential. Turmeric extract nanoemulsion has an antibacterial effect against MRSA in vitro.